Pulmonary adenocarcinoma with mucin production modulates phenotype according to common genetic traits: a reappraisal of mucinous adenocarcinoma and colloid adenocarcinoma. (22nd March 2017) - Sonzogni, Angelica; Bianchi, Fabrizio; Fabbri, Alessandra; Cossa, Mara; Rossi, Giulio; Cavazza, Alberto; Tamborini, Elena; Perrone, Federica; Busico, Adele; Capone, Iolanda; Picciani, Benedetta; Valeri, Barbara; et al.
Abstract: Whether invasive mucinous adenocarcinoma (IMA) and colloid adenocarcinoma (ICA) of the lung represent separate tumour entities, or simply lie within a spectrum of phenotypic variability, is worth investigating. Fifteen ICA, 12 IMA, 9 ALK ‐rearranged adenocarcinomas (ALKA), 8 non‐mucinous KRAS ‐mutated adenocarcinomas (KRASA) and 9 mucinous breast adenocarcinomas (MBA) were assessed by immunohistochemistry for alveolar (TTF1, cytoplasmic MUC1), intestinal (CDX‐2, MUC2), gastric (membrane MUC1, MUC6), bronchial (MUC5AC), mesenchymal (vimentin), neuroendocrine (chromogranin A, synaptophysin), sex steroid hormone‐related (oestrogen and progesterone receptors), pan‐mucinous (HNF4A) and pan‐epithelial (keratin 7) lineage biomarkers and by targeted next generation sequencing (TNGS) for 50 recurrently altered cancer genes. Unsupervised clustering analysis using molecular features identified cluster 1 (IMA and ICA), cluster 2 (ALKA and KRASA) and cluster 3 (MBA) ( p < 0.0001). Cluster 1 showed four histology‐independent sub‐clusters (S1 to S4) pooled by HFN4A and MUC5AC but diversely reacting for TTF1, MUC1, MUC2, MUC6 and CDX2. Sub‐cluster S1 predominantly featured intestinal‐alveolar, S2 gastrointestinal, S3 gastric and S4 alveolar differentiation. In turn, KRASA and ALKA shared alveolar lineage alongside residual MUC5AC expression, with additional focal CDX2 and diffuse vimentin, respectively. A proximal‐to‐distal scheme extending from terminal (TB) and respiratory (RB) bronchioles to alveolar cells was devised, where S3 originated from distal TB (cellular mucinous adenocarcinoma), S2 from proximal RB (secreting mucinous adenocarcinoma), S1 from intermediate RB (mucin lake‐forming colloid adenocarcinoma), S4 from distal RB (colloid alveolar adenocarcinoma), KRASA from juxta‐alveolar RB (KRAS‐mutated non‐mucinous adenocarcinoma) and ALKA from juxta‐bronchial alveolar cells (ALK‐translocated adenocarcinoma). TNGS analysis showed KRAS, LKB1, TP53, APC and CDKN2A mutation predominance. In conclusion, IMA and ICA are basket categories, which likely originate from distinct domains of stem/progenitor cells spatially distributed along bronchioles upon common molecular features and genetic alterations.